Experimental Study of an Aquaponic System with Leeks and a Fish Pond: Effectiveness and Productivity: Studi Experimental Sistem Aquaponik dengan Daun Bawang dan Kolam Ikan: Efeksitas dan Produktivitas - Handoko, Muhammad; Miftakhurrohmat, A. (Universitas Muhammadiyah Sidoarjo, 2025)
The growth of shallot plants using conventional soil methods is often constrained by the limited efficiency of water use and uneven nutrient availability. This study aims to analyze the effectiveness of an aquaponic system with various growing media (gravel, charcoal, cocopeat, and hydroton) compared to conventional soil cultivation. The experimental method was conducted by observing leaf length (cm) and the number of leaves over 15 days in each growing medium. The results showed that the aquaponic system significantly enhanced shallot growth compared to the soil method. Hydroton medium provided the best results, with leaf length reaching 28 cm and 7 leaves within 15 days, outperforming other media. Growth efficiency in hydroton reached 84.21% at the 5-day observation. The study concludes that the aquaponic system is more efficient in supporting shallot growth than the soil method, offering better water savings, more consistent nutrient availability, and supporting the concept of sustainable agriculture.